Effect of Deep Inspiration and Expiration on QTc Interval in Normal Healthy Subjects - Gautam, Y; Bade, M (Kathmandu University medical journal, 2018)
Background It is a well known fact that phases of respiration cause change in heart rate and autonomic tone of the heart. But how cardiovascular autonomic reflexes affect the electrocardiographic Heart rate-corrected QT interval (QTc) during the inspiratory and expiratory phase of respiration also need to be established. Objective To determine whether the respiratory phases influence the QTc interval or not. Method This was a quantitative, observational, cross-sectional study done at Kathmandu University School of Medical Sciences, Pre-Clinical Basic Science Block, Chaukot. Total one hundred students between 18 to 25 years of age, studying at KUSMS Pre-clinical science Block were included. QTc interval was recorded for normal respiration, deep inspiration and deep expiration by electrographic recording using ADInstruments. The values obtained were later analyzed using paired t-test in SPSS 16.0. Result The mean QTc interval during normal respiration was 392.1±21.6 milliseconds, during deep inspiration was 384.2±15.5 milliseconds and that following deep expiration was 395.0±13.1 milliseconds. There was no significant difference between QTc interval at the end of deep inspiration (p value < 0.05) and QTc interval at the end of deep inspiration (p value < 0.05) when compared with normal respiration. Conclusion This study shows that neither the inspiratory phase nor expiratory phase alters the QTc interval in normal healthy individual. Thus, it can also be implied that alteration in inspiratory and expiratory phase in various respiratory diseases does not cause any change in QTc interval.